Trauma-Related Psychopathology in Iraqi Refugee Youth Resettled in the United States, and Comparison With an Ethnically Similar Refugee Sample: A Cross-Sectional Study - Grasser, Lana Ruvolo; Haddad, Luay; Manji, Suzanne; Assari, Shervin; Arfken, Cynthia; Javanbakht, Arash (Frontiers in Psychology, 2021)
Background: Warzone exposure and forced migration has unique acute and chronic impacts on youth, yet effects of exposure may not be universal across diverse refugee groups. Understanding how youth from various refugee groups are differentially affected by stress and trauma is critical to allocate resources and implement screening measures with the goal of providing early intervention. Method: A convenience sample of 48 Iraqi refugee youth ages 6-17 was assessed within the first month of arrival to the United States. Youth provided self-reported severity of posttraumatic stress and anxiety symptoms; symptoms severity was then compared with an existing sample of 135 Syrian refugee youth to explore whether refugee youth of different nationalities experience the same effects of warzone exposure and forced migration. Results: Severity of separation anxiety and negative alterations in cognition and mood were the greatest symptomatic concerns in Iraqi refugee youth. 38% of responding Iraqi youth showed possible indication of an anxiety disorder. Severity of posttraumatic stress symptoms were lower in Iraqi youth compared to Syrian youth. Both groups reported high levels of separation anxiety. Conclusion: The present study indicated that Iraqi refugee youth experience a range of anxiety and posttraumatic stress symptoms, which were less severe in Iraqi versus Syrian youth. Comparing refugee youth of different nationalities is of particular importance, as our results demonstrate that findings from one refugee population cannot easily be generalized to another. Clinical and research efforts should prioritize interventions to address separation anxiety in refugee youth, which was of concern in both samples.